Hip Pain and Mobility Deficits-Hip Osteoarthritis: Revision 2017 Clinical Practice Guidelines Linked to the International Classification of Functioning, Disability and Health - The Orthopaedic Section of the American Physical Therapy Association (康复学报, 2019)
The Orthopaedic Section of the American Physical Therapy Association(APTA)has an ongoing effort to create evidence-based practice guidelines for orthopaedic physical therapy management of patients with musculoskeletal impairments described in the World Health Organization's International Classification of Functioning, Disability, and Health(ICF).The purpose of these revised clinical practice guidelines is to review recent peer-reviewed literature and make recommendations related to hip pain and mobility deficits.